What drives cash demand? Transactional and residual cash demand in selected countries - Balázs Sisak (Magyar Nemzeti Bank, 2011)
The goal of this study is to determine the reasons behind high cash demand in several Central European countries, especially Hungary. We distinguish between legal and illegal cash demand in an attempt to model the former. In our approach, legal cash demand can be explained by transactional and saving motives (hoarding). We apply both direct calculation and an econometric approach in order to isolate transactional demand. Regarding the econometric approach, a number of different models are estimated to eliminate, as far as possible, endogeneity bias. We examine transactional and residual cash stock (legal hoarding and illegal cash demand) of several Central European and Western countries that have their own currency (did not introduce euro). We find that transactional cash demand is strongly influenced by the level of improvement of the payment system. There are explicit signs that interest rates negatively influence nontransactional cash demand. However, we find examples where this is not the case. In these instances, the increase of non-transactional cash demand may be caused by illegal cash demand.
Keywords: E26; E41; E42; C23; 330; cash demand; shadow economy; payment system; panel econometrics